PENGARUH KEPERCAYAAN, KEPUASAN PELANGGAN DAN KOMITMEN HUBUNGAN TERHADAP EKUITAS MEREK DAN CITRA BANK SYARIAH XYZ DI KOTA JAMBI - Lucky Enggrani (Jurnal Manajemen Terapan dan Keuangan, 2012)
With the aim of increasing the market share and improving the image of Islamic banking, one of the marketing activities performed towards the brand equity and the image of Islamic bank is the concept of relationship marketing. The key factor of this concept is the implementation of trust, customer satisfaction, and relationship commitment. The aim of this research is to find out the influence of trust, customer satisfaction, and relationship commitment to the brand equity and the image of Islamic bank. This research is conducted at XYZ Bank customers in Jambi with a total sample of 200 respondents obtained by using convenience sampling. The method used in this research is path analysis processed by using AMOS 5. The result of this research shows that trust variable indirectly affects the brand equity through brand awareness and brand loyalty variable. In addition, trust variable directly influences the image of Islamic bank. The trust variable has the most influence on brand equity and the image of Islamic bank compared to the customer satisfaction variable and relationship commitment.